Effects of intermittent hypoxic training on acclimatization in elite cross-country skiers - Richalet, J.-P.; Brugniaux, J.; Schmitt, L.; Jeanvoine, H.; Nicolet, G.; Duvallet, A.; Fouillot, J. P.; Robach, P. (13. International Hypoxia-Symposium, February, 19-22, 2003, Banff, Alberta (Kanada), 2003)
The purpose of this study was to evaluate the consequences of intermittent exposure to high altitude ("live high—train low") on clinical status and physiological markers of acclimatization during a training session of elite cross-country skiers. METHODS: eleven athletes (6 men, 5 women) performed a 18-day training period at 1100m, by sleeping either at 1100m (group C, n 5 5) or in hypoxic rooms (group H, n 5 6) at simulated altitudes of 2500m, 3000m and 3500m (3 3 6 days). Lake Louise AMS score and arterial oxygen saturation (SaO2) during sleep were measured daily. Cardiac function (echocardiography) and ventilatory response to hypoxic exercise (HVRe, 30% normoxic VO2max) were evaluated at 1100m before and 15 days after the training session. RESULTS: Subjects did not complain of headache, gastrointestinal or dizziness symptoms. Fatigue and sleep disturbances were frequently mentioned but there was no significant difference between the two groups. In group H, interventricular septum thickness increased from 10.3 6 0.8 to 11.2 6 1.3 (p , 0.05), 4 out of 6 subjects showed a 5 to 10 mmHg increase in pulmonary arterial pressure. One subject showed a 6 mm increase in right ventricular end diastolic diameter. Mean nocturnal SaO2 at high altitude was 93.6, 91.7 and 89.8% at 2500, 3000 and 3500m, respectively. Three subjects showed a marked desaturation during the first two days after switching to a higher altitude (mean SaO2 86% at 3500m). No significant change was observed in HVRe or hypoxic exercise-induced desaturation 14 days after the training session. None of these parameters were correlated with the observed changes in performance (VO2max). CONCLUSION: sleeping during 18 days in hypoxic chambers (up to 3500m), while training at 1100m did not induce any significant clinical disorder; however cardiac morphological changes may occur as a result of prolonged increase in pulmonary pressure. Nocturnal saturation should be monitored to detect marked desaturation. Signs of ventilatory acclimatization had disappeared 15 days after the hypoxic exposure. This study was supported by grants from the International Olympic Committee and the French Ministry of Sports.